Participant perspectives of an online co‐design process to develop a prevention‐focused mental health and well‐being platform for primary producers. (26th August 2022) - Binder, Marley J.; Beks, Hannah; Versace, Vincent L.; Macdonald, Joanna; Mckay, Claire; Cunningham, Sally; Wall, Gavin; Barnes, Kelly; Cornell, Sarah; Cock, Malcolm; Kennedy, Alison; Namara, Kevin Mc
Abstract: Objective: To explore participant experiences of an online co‐design process to develop a web‐based preventative mental health and well‐being intervention targeting primary producers in rural Australia. Setting: Rural Victoria, Australia. Participants: Participants from a primary producer background, including horticulture, fisheries, animal cultivation and farm consultancy, were eligible for the study if they had participated in both the co‐design and beta testing processes for a primary producer platform. Design: A qualitative study using semi‐structured phone‐based interviews was undertaken. A reflexive inductive approach to data analysis was employed to develop themes. Results: Eleven participants were interviewed, with an average age of 51 years, of which 7 were female. Five main themes were developed. These included: (1) participant diversity, (2) impact of online delivery on co‐design participation, (3) experiences of the co‐design process, (4) maintaining a shared vision and goals and (5) acting on the co‐design recommendations. Use of online methods was a clear enabler to engage participants who were geographically dispersed and offers an alternative to more conventional approaches to co‐design using face‐to‐face methods. Some aspects of participant engagement may need a greater focus when conducted online compared with face‐to‐face. Conclusions: Using an online co‐design method to develop a preventative mental health and well‐being web‐based platform for primary producers was novel. Findings address a gap in the literature around the experience of participants engaging in a co‐design process and identify opportunities to improve participant engagement and experience with the online format.